Healthcare service quality measurement in Malaysia : A scoping review - Keng Sheng, Chew; Shirly Siew Ling, Wong; Ke, Lin Siew; Rossazana Ab-Rahim, Ab-Rahim (Malaysian Medical Association, 2023)
Introduction: Although healthcare service industry has been thriving in Malaysia, the types of healthcare service quality models used in past research as well as their key messages had not been explored. A scoping review was performed to determine the validated healthcare service quality models, the key messages of these past studies and potential research gaps that should be addressed in future studies.